Estimation of Parameters (Serum Glucose, Urea, Creatinine And C-Peptide) in Diabetic Nephropathy - Rukia A. Jassim1 , Zeena A. Alsaady2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Diabetes mellitus is a metabolic disorder of multiple aetiology. Destruction of pancreatic beta cells, hyperglycaemia, and insulin deficiency cause type 1 diabetes mellitus. Diabetic nephropathy is the damage to kidneys because of diabetes. It is predominantly seen in patients with type 1 diabetes (insulin-dependent type) and type 2 diabetes (non-insulin-dependent type). An active peptide hormone, C-peptide has the likelihood of causing major physiological effects. C-peptide is the best indication of endogenous insulin secretion occurring in patients with diabetes. In this regard, the current study undertakes a comprehensive study of C-peptide and kidney (renal) failure in patients with diabetes mellitus type 1 , in order to assess their association . The subjects for this study were (70) patients with type 1 DM and ( 65) patients with diabetic nephropathy in different age and both sex , Laboratory tests such as (serum creatinine, urea, glucose, albumin , total protein and fasting serum C-peptide, are conducted. Data was compare the values between different category patients.